2018
DOI: 10.1111/sltb.12516
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Exposure in Law Enforcement Officers

Abstract: Objective To examine occupational and personal suicide exposure among Law Enforcement Officers (LEOs) and related mental health outcomes. Methods Law Enforcement Officers (N = 813) completed an online survey about their suicide exposure, whether scenes stayed with them, and current symptoms of depression, anxiety, PTSD, and suicidal ideation. Results Almost all participants (95%) had responded to at least one suicide scene with an average of 30.90 (SD = 57.28) career suicide scenes and 2.17 in the last year (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Some of the most tangible of these trauma experiences were reported by those practitioners who were either present at the time of the death, who interacted with the body of the deceased, or who imagined what the death may have looked like. Previous research has found that train drivers who witness a death find the visual experience to be the most distressing aspect and law enforcement officers exposed to suicide scenes experience increased post-traumatic symptoms [45,46]. This suggests that visual experience may heighten trauma responses.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most tangible of these trauma experiences were reported by those practitioners who were either present at the time of the death, who interacted with the body of the deceased, or who imagined what the death may have looked like. Previous research has found that train drivers who witness a death find the visual experience to be the most distressing aspect and law enforcement officers exposed to suicide scenes experience increased post-traumatic symptoms [45,46]. This suggests that visual experience may heighten trauma responses.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to suicide is a known risk factor for further suicide (Pitman et al, 2016). Research with other first responders such as the police and firefighters demonstrates that these staff may be exposed on average to 30 such events during their working lives (Cerel et al, 2018), with higher levels of suicidality than other professionals (Stanley et al, 2016). Such cumulative exposure may increase the risk of suicide among first responders (Kimbrel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 11 papers assessed suicide impacts among psychiatrists and psychologists only [4,[28][29][30][31][32][33][34][35][36][37], one assessed the suicide impact on nurses [38] and one assessed exposure to suicide reactions among counselors and social workers [39]. Only five papers addressed exposure to suicide among first responders (firefighters and police) [3,[40][41][42][43]. The findings of each paper are summarized on the Table 1.…”
Section: Literature Characteristicsmentioning
confidence: 99%
“…In this review, we are particularly interested in two groups of people, who because of their occupations, have greater exposure to suicide than the rest of the population; mental health professionals and first responders [3,4]. As well as having greater than usual exposure to suicide, these groups are distinct from bereaved family and friends due to the professional nature of their relationship with the person who died by suicide.…”
Section: Introductionmentioning
confidence: 99%